2020
DOI: 10.1016/j.ihj.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the acute conversion and maintenance of sinus rhythm in rheumatic atrial fibrillation using oral flecainide

Abstract: Background Achievement of sinus rhythm (SR) is an important goal in rheumatic atrial fibrillation (AF). Studies in rheumatic AF have often used amiodarone for rhythm control. Flecainide has not been studied in these patients due to concerns of underlying structural heart disease. Methods Pharmacological cardioversion by oral single loading dose (SLD) of Flecainide (4 mg/kg, ≤300 mg) was tested in 50 patients with rheumatic AF (MVA 1.51 ± 0.19 mm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In a pilot study of 50 rheumatic AF patients, a single oral dose of 4 mg/kg of flecanide effectively cardioverted 4% to sinus rhythm, and 72% achieved sinus rhythm with direct current cardioversion (DCCV). 42 In a study of 165 patients with rheumatic AF, ibutilide successfully restored sinus rhythm in 77%, with a mean conversion time of 7.9 ± 4.1 minutes. Torsades de pointes requiring defibrillation developed in 1.8% of patients at a mean interval of 55 ± 37 minutes, and there were no deaths.…”
Section: Rhythm Control In Rheumatic Afmentioning
confidence: 99%
See 2 more Smart Citations
“…In a pilot study of 50 rheumatic AF patients, a single oral dose of 4 mg/kg of flecanide effectively cardioverted 4% to sinus rhythm, and 72% achieved sinus rhythm with direct current cardioversion (DCCV). 42 In a study of 165 patients with rheumatic AF, ibutilide successfully restored sinus rhythm in 77%, with a mean conversion time of 7.9 ± 4.1 minutes. Torsades de pointes requiring defibrillation developed in 1.8% of patients at a mean interval of 55 ± 37 minutes, and there were no deaths.…”
Section: Rhythm Control In Rheumatic Afmentioning
confidence: 99%
“…DCCV is effective and safe in restoring sinus rhythm in most rheumatic AF patients, especially after valvular interventions such as balloon valvotomy. 42 To improve cardioversion success and prevent relapses, DCCV should be done after at least 1 month of oral amiodarone loading. 45 …”
Section: Rhythm Control In Rheumatic Afmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Other studies have elucidated potential AF rate and rhythm management strategies specific to those with RHD. 13 , 14 , 15 , 16 , 17 , 18 , 19 Nonetheless, there remains a paucity of data to guide management of AF in patients with RHD within their respective local contexts. National and regional health metrics are essential in guiding implementation strategies and policy interventions to improve health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that oral flecainide was effective in maintaining SR in patients with rheumatic AF, following previous balloon mitral valvotomy (BMV). 16 In this prospective single center stud, we assessed the safety and efficacy of oral flecainide in rheumatic AF following mitral valve replacement.…”
Section: Introductionmentioning
confidence: 99%